Two new species of Haploperla (Plecoptera: Chloroperlidae) from China - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2016)
Two new species of the chloroperline genus Haploperla, H. tuanjiena sp. nov. from Sichuan Province, China and H. datongensis sp. nov. from Qinghai Province, China are described and illustrated. Haploperla tuanjiena is characterized by terga 10 with a medially triangular sclerotized area and the epiproct subtriangular, anterolateral margin sclerotized with apex acute. Haploperla datongensis is characterized by the epiproct tongue-shaped, anterior margin and anteroventrally strongly sclerotized. The new species are compared with similar taxa of the genus. An identification key is provided for the seven known Chinese species of Haploperla.